Change your space, change your culture : how engaging workspaces lead to transformation and growth - Miller, Rex; Casey, Mabel; Konchar, Mark (Wiley, 2014)
The fastest, easiest way to shift culture toward engagement and productivity Change Your Space, Change Your Culture is a guide to transforming business by rethinking the workplace. Written by a team of trail-blazing leaders, this book reveals the secrets of companies that discovered the power of culture and space. This insightful guide reveals what companies lose by viewing office space as something to manage or minimize. With practical tips and implementation details, the book helps the reader see that the workspace is, in fact, a crucial driver of productivity and morale.